Symptomless turnip yellows virus infection causes grain yield loss in lentil and field pea: A three-year field study in south-eastern Australia - Nancarrow, Narelle; Aftab, Mohammad; Hollaway, Grant; Rodoni, Brendan; Trębicki, Piotr (Frontiers in Plant Science, 2022)
Turnip yellows virus (TuYV) is a damaging virus that is persistently transmitted by aphids and infects a wide range of grain hosts including lentil (Lens culinaris Medik), field pea (Pisum sativum L.) and canola (Brassica napus L., oilseed rape). Although information is available about the effects of TuYV infection on grain yield in canola, data about its impact on yield in pulses is lacking. In this study, field experiments quantifying the effects of TuYV infection on the grain yield of lentil and field pea were conducted over three consecutive years (2018-2020) with varying weather conditions. Plants artificially inoculated with TuYV using viruliferous green peach aphid (Myzus persicae, Sulzer) were grown under typical field conditions in south-eastern Australia. At maturity, grain yield, along with associated grain and plant growth parameters, were measured. Compared to the non-inoculated control treatment, early TuYV infection reduced grain yield by up to 36% in lentil and 45% in field pea, while late TuYV infection had no significant impact on yield. Despite a high incidence of TuYV infection and significant yield losses recorded in inoculated plots, no obvious symptoms of virus infection were observed in the inoculated plots in any of the six experiments; this lack of visible symptoms in lentil and field pea has significant implications for crop health assessments, demonstrating the importance of testing for virus instead of relying solely on the presence of visual symptoms, and may also be leading to an underestimation of the importance of TuYV in pulses in Australia.